A Potential Vorticity Signature for the Cold Sector of Winter Extratropical Cyclones - Vanniere,B; Czaja,A; Dacre,H; Woollings,T; Parfitt,R (Quarterly Journal of the Royal Meteorological Society, 2016)
The cold sector of mid-latitude storms is characterised by distinctive features such as strong surface heat fluxes, shallow convection, convective precipitation and synoptic subsidence. In order to evaluate the contribution of processes occurring in the cold sector to the mean climate, an appropriate indicator is needed. This study describes the systematic presence of negative PV behind the cold front of extratropical storms in winter. The origin of this negative PV is analysed using ERA-Interim data, potential vorticity tendencies averaged over the depth of the boundary layer are evaluated. It is found that negative PV is generated by diabatic processes in the cold sector and by Ekman pumping at the low centre, whereas positive PV is generated by Ekman advection of potential temperature in the warm sector. We suggest here that the negative PV at low-levels can be used to identify the cold sector. A PV-based indicator is applied to estimate the respective contributions of the cold sector and the remainder of the storm to upward motion, and large scale and convective precipitation. We compare the PV-based indicator with other distinctive features that could be used as markers of the cold sector, and find that potential vorticity is the best criterion when taken alone, and the best when combined with any other.